The impact of Gap years on career purpose and employability - Angelis, Chiara de (2021)
The Impact Of Gap Years On Career Purpose And EmployabilityThe gap year is a growing practice in several countries. Numerous scientific articles demonstrated that it is an enriching experience. Following a qualitative method, this research analyzed the impact of one or more gap years on people’s employability. In particular, it aimed to study the gap year influence both on students who have not entered the labor market yet and on professionals who have already undertaken a professional path. By investigating different aspects, the study found that this experience positively affects individuals’ career and employability.